(untitled) (Palíndromo, 2013)
This paper delves into the book La chambre claire written by Roland Barthes and compares the concepts of studium and punctum, conceived within this text, to the opposing poles that defines the mnemonic human faculty according to Paul Ricœur’s phenomenology of memory. The link between the memory and the photographic image, by its turn, lies in the detachment principle implied in both: if memory, as Aristotle says, “is of the past” and relies on the temporal distinction between the recollection and the object or event accounted by this recollection, the photographic image, due to the relationship of contiguity established with its referent, implies on the demarcation of a temporal detachment between sign and its referent. From the recognition of similarities between the photography and the phenomenology of memory, this study aims to establish the common aspects that both operations has in their relationship with time.